Monometal and Competitive Adsorption of Cd, Ni, and Zn in Soil Treated with Different Contents of Cow Manure - Mostafa Chorom; Rahim Mohammadzadeh Karkaragh; Babak Kaviani; Yusef kianpoor Kalkhajeh (Applied and Environmental Soil Science)
This study was conducted to assess the monometal and competitive adsorption of Cd, Ni, and Zn in the soil incubated with different contents of decayed cow manure (: 0, : 25, and : 50 tha−1) for 90-d at 25°C. Sorption isotherms were characterized using the linear Freundlich equation. Most sorption isotherms were well described by the Freundlich equation (maximum and minimum ) and the monometal and competitive adsorption isotherms of Zn, Cd, and Ni followed the L-curve type (L-2). Results showed that the mono- and multimetal sorption amounts increased with an increase in organic amendment content as the sorption capacities for Cd, Ni, and Zn followed the following sequence: . This sequence was consistent with the CEC and particularly pH for the three soils. All soils showed greater sorption capacity for Zn than the other trace elements as the sorption sequence in was , while in both and was . Therefore, the metal-binding sites in OM were more selective for Zn and Ni than Cd. Competition significantly reduced metals , especially for Cd and Ni.